1985
DOI: 10.1161/01.atv.5.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipoprotein levels in treated and untreated hypertensive men and women. The National Heart Foundation of Australia Risk Factor Prevalence Study.

Abstract: Experimental studies have reported that common antihypertensive drugs such as diuretics, beta-blockers, and methyldopa have adverse effects on plasma lipids and lipoproteins. To investigate whether such effects can be observed in the general population, plasma lipid and lipoprotein levels were compared in subjects receiving antihypertensive treatment, subjects with untreated high blood pressure, and subjects with normal blood pressure in a random sample of 5603 subjects screened in a national study of risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Both high blood pressure and elevated serum lipids are major risk factors for the development of ischemic heart disease (IHD) or CAD, and their progression is accelerated among diabetics. Furthermore, these metabolic abnormalities are also associated with macrovascular and microvascular complications of type 2 diabetes and risk factors for atherosclerosis in children and young adults [7][8][9][10].Current research literature has shown that diabetes mellitus is a cardio-vascular risk equivalent and has been further confirmed by Framingham study and other landmark studies [11,12]. Diabetic dyslipidemia is defined as elevated triglyceride, elevated low-density lipoprotein cholesterol (LDL-C) and low high density lipoprotein cholesterol (HDL-C) levels [13].…”
Section: Introductionmentioning
confidence: 99%
“…Both high blood pressure and elevated serum lipids are major risk factors for the development of ischemic heart disease (IHD) or CAD, and their progression is accelerated among diabetics. Furthermore, these metabolic abnormalities are also associated with macrovascular and microvascular complications of type 2 diabetes and risk factors for atherosclerosis in children and young adults [7][8][9][10].Current research literature has shown that diabetes mellitus is a cardio-vascular risk equivalent and has been further confirmed by Framingham study and other landmark studies [11,12]. Diabetic dyslipidemia is defined as elevated triglyceride, elevated low-density lipoprotein cholesterol (LDL-C) and low high density lipoprotein cholesterol (HDL-C) levels [13].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The excess prevalence of cardiovascular risk factors in hypertensives has been considered to be due to the effects of obesity. More recently it has been proposed that hypertension is part of a cluster of metabolic risk factors (a metabolic syndrome X) involving hyperlipidaemia and hyperglycaemia, with insulin resistance or hyperinsulinaemia as the common link.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study is: (1) to examine the prevalence of the metabolic syndrome and its component variables and their relationship to body mass index (BMI) and insulin levels in a general population; (2) to examine the distribution and clustering of metabolic variables in hypertensive and normotensive men; and (3) to determine the extent to which these relationships are associated with serum insulin and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have now demonstrated that hypercholesterolemia increases the vascular response to vasoconstrictors such as NE and impairs vasodilation in large and small arteries (1,2). By increasing peripheral vascular resistance, cholesterol may contribute to elevating arterial pressure and account for the frequently observed association between hypercholesterolemia and hypertension in humans (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%